Comparison of high-fat style diet-induced dysregulation of baroreflex control of renal sympathetic nerve activity in intact and ovariectomized female rats - Sucedaram, Yamuna; Johns, Edward James; Husain, Ruby; Sattar, Munavvar Abdul; Abdulla, Mohammed; Khalilpourfarshbafi, Manizheh; Abdullah, Nor Azizan (SAGE Publications, 2020)
The present study compared high-fat style diet (HFSD)-induced renal nerve-dependent dysregulation of the baroreflex control of renal sympathetic nerve activity (RSNA) in ovary-intact and ovariectomized (OVX) rats. Female rats received a normal diet (ND) or a HFSD for 10 weeks prior to the acute study. The rats were anesthetized; RSNA and heart rate (HR) were measured. Acute bilateral renal denervation was performed, and baroreflex gain curves were constructed from the baroreflex changes in RSNA to vasopressor and vasodepressor drugs. Cardiopulmonary baroreflex control of RSNA was assessed by acute saline volume expansion (VE). Mean blood pressure was elevated in the OVX-HFSD rats compared to the HFSD group reaching significance on week 6 of the experimental study (P < 0.01). Adiposity index and creatinine clearance were significantly greater in all HFSD rats compared to their ND counterparts. Fractional excretion of sodium rose initially in all HFSD rats but was normalized towards the end of the study although absolute sodium excretion remained high. In the acute study, baroreflex gain curve sensitivity (A2) of RSNA was similarly decreased in both the HFSD and OVX-HFSD rats by 88% (P < 0.005) and 94% (P < 0.001) respectively compared to their control counterparts, but was normalized following bilateral renal denervation. VE-reduced RSNA in ND and OVX-ND rats by 55% and 52% (both P < 0.001) respectively, but did not alter RSNA in both HFSD and OVX-HFSD female rats. Following bilateral renal denervation, HFSD and OVX-HFSD rats exhibited 37% (P < 0.01) and 24% (P < 0.01) reduction in RSNA respectively. These findings demonstrate that although obesity-induced impairment of baroreflex control of RSNA occurred similarly in HFSD and OVX-HFSD rats, mean blood pressure was increased only in the ovarian hormones deprived-group suggesting that ovarian hormones could have modulatory role on other mechanisms that regulate blood pressure in female obesity. Impact statement: Over activation of renal sensory nerve in obesity blunts the normal regulation of renal sympathetic nerve activity. To date, there is no investigation that has been carried out on baroreflex regulation of renal sympathetic nerve activity in obese ovarian hormones deprived rat model, and the effect of renal denervation on the baroreflex regulation of renal sympathetic nerve activity. Thus, we investigated the role of renal innervation on baroreflex regulation of renal sympathetic nerve activity in obese intact and ovariectomized female rats. Our data demonstrated that in obese states, the impaired baroreflex control is indistinguishable between ovarian hormones deprived and non-deprived states. This study will be of substantial interest to researchers working on the impact of diet-induced hypertension in pre- and postmenopausal women. This study provides insight into health risks amongst obese women regardless of their ovarian hormonal status and may be integrated in preventive health strategies. © 2020 by the Society for Experimental Biology and Medicine.